Design of an Electronic UV Sterilization Camera for Medical Protection Equipment Against COVID 19 - Oscar Mauricio (2020)
The present research is of an applicative - experimental type whose objective was to design an electronic UV sterilization chamber for medical protection equipment against COVID19. This biomedical equipment has a PID control that is executed through the application of digital programming to control the UV lamp that emits Ultra Violet type C radiation. Within the power control design for the activation of the sterilization lamp UV, is considered a pulse provided by the Arduino Nano development board, as a result of the design of the PID controller of the preceding stage that activates a MOC3031 optocoupler composed of a light emitting diode and a triac that allows the enablement of loads with peak voltage from 250 to 400V, so they are very suitable for activating the UV-C radiation lamp. It also features a closure control that provides user safety so that UV light does not cause injury. The results obtained were effective since the use of type C ultraviolet light alters the composition of nucleic acids, breaking the DNA and RNA bonds of viruses, bacteria and primitive microorganisms, due to the exposure of radiation with a 254nm peak wavelength. This break in the DNA or RNA material prevents the microorganism from replicating. Therefore, it shows an efficacy for the disinfection and sterilization of medical personal protective equipment (masks, aprons among others) of health professionals.